Dampak Desa Wisata Terhadap Kesejahteraan Masyarakat (Studi Deskriptif di Desa Ketambe, Kec. Ketambe) - Supranata, Gunawan (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
This study examines the management of Ketambe Tourism Village and its impact on the welfare of local communities. The problem studied is how the development of creative economy-based tourism can improve economic, social, and environmental aspects. The purpose of this study is to analyze the management of tourism villages in achieving community welfare. The research method used is qualitative with a descriptive approach. Research informants consist of local communities, tourism village managers, and relevant stakeholders. Data collection techniques include in-depth interviews and direct observation. The collected data were analyzed using descriptive analysis methods to determine the actual conditions from the interview results. The results of the study indicate that community-based tourism management in Ketambe Tourism Village has succeeded in increasing community income through the provision of accommodation, tour guides, and local products. In addition, tourism in Ketambe also contributes to the preservation of local culture. However, environmental challenges such as river abrasion and illegal logging still need to be addressed. This study recommends sustainable management and collaboration between the government, community, and non-governmental organizations to ensure that economic benefits do not harm the environment.